Characterization, fractionation and mobility of trace elements in surface sediments of the Jequiezinho River, Bahia, Brazil - SILVA,DARCI S. (2020)
Abstract The Jequiezinho River is a temporary river. In the urban stretch it is impacted, with perennial flow coming from domestic sewage and rainwater. This study evaluated the geochemical distribution and potential mobility of some metals (Pb, Co, Ca, Cr, Mg, Cu, Fe, Mn, Ni and Zn) in sediments of the Jequiezinho River. Sediment samples were collected at ten different sites along the river. The silt/clay fraction was submitted to acid digestion and sequential extraction with analysis by FAAS. The results indicated that, in the more densely populated region, there was an increase in concentrations of Cr, Ni, Cu, Co, Pb, and Zn. The contents found were compared with the guideline values of TEL (Threshold Effect Levels) and PEL (Probable Effect Levels)​​, not exceeding the maximum reference limits. The results indicated that Ca, Mg, Mn and Fe presented greater susceptibility to mobility and bioavailability suggesting the geochemical origin responsible for these high concentrations. The multivariate analysis showed that Cr, Ni, Cu, Co, Pb, and Zn presented a similar behavior, especially in locations with higher population density and the discharge of non-discriminated effluents, reflecting the anthropogenic contributions as responsible for the concentration increase.